The Influence of Macroeconomics on Credit Risk with Bank Size as a Moderating Variable - Fariabi, Muhammad Rofi; Riharjo, Ikhsan Budi (LifeSciFi, 2026)
This study is motivated by the vulnerability of regional development banks to credit risk amid macroeconomic fluctuations and the inconsistency of previous research findings. The aims of this study is to analyze the effects of inflation, gross domestic product, exchange rates, and the policy interest rate on credit risk, as well as the moderating role of bank size in 27 regional development banks in Indonesia during the 2020–2024 period. The study employs a causal quantitative approach using a saturated sampling technique (524 observations) and Moderated Regression Analysis. The results show that inflation, gross domestic product, and the policy interest rate have a positive and significant effect on credit risk, while the exchange rate has a negative and significant effect. Bank size is proven to moderate all macroeconomic variables by weakening the effects of inflation, gross domestic product, and the policy interest rate, while strengthening the effect of exchange rates on credit risk. These findings imply that strengthening bank assets and size is a crucial factor in enhancing the resilience of regional development banks in facing economic pressures to maintain credit quality stability.